Synthesis and characterization of nanoparticles Zn0.7Ni0.15Cu0.15Fe2O4 using the co-precipitation method. Issue 1 (May 2021) - Sagala, L P S; Humaidi, S; Tarigan, K; Soehada, A M S; Sebayang, P
Abstract: This research was conducted to see the nanostructure and magnetic properties of nanoparticle Zn0.7 Ni0.15 Cu0.15 Fe2 O4 . Zn0.7 Ni0.15 Cu0.15 Fe2 O4 has been successfully synthesized at 100°C using co-precipitation method. After synthesized, it was dried at 80°C. The second step, nanoparticle powder was characterised by X-Ray Diffraction (XRD) to determine the structure and phases formation of Zn0.7 Ni0.15 Cu0.15 Fe2 O4 . FE-SEM was used to analyze the morphology of Zn0.7 Ni0.15 Cu0.15 Fe2 O4 . To find out the elements contained in the sample, EDAX testing was conducted. X-Ray Diffraction (XRD) results showed that Zn0.7 Ni0.15 Cu0.15 Fe2 O4 in the shape of cubic spinel with the main peak at (311). There was a hematite phase (Fe2 O3 ) with low intensity. Zn0.7 Ni0.15 Cu0.15 Fe2 O4 crystallizes well indicated by 2θ = 35.385°. The crystal size on the nano scale has been formed, which was 14.5087 nm. The FE-SEM results showed that the morphology of Zn0.7 Ni0.15 Cu0.15 Fe2 O4 was spherical and has agglomerated. The elements contained in these nanoparticles were Zn, Ni, Cu, Fe and O. There were no other impurities indicated from the EDAX test results.This indicated that the elements contained were already in accordance with the chemical formula. Magnetic hysteresis curves showed that Zn0.7 Ni0.15 Cu0.15 Fe2 O4 was softmagnetic.